Canine oral squamous cell carcinoma as a spontaneous, translational model for radiation and immunology research - Boss, Mary-Keara; Harrison, Lauren G.; Gold, Alexandra; Karam, Sana D.; Regan, Daniel P. (Frontiers in Oncology, 2023)
Improving outcomes for oral squamous cell carcinoma (OSCC) patients has been hindered by a lack of effective predictive animal models. Spontaneously occurring canine OSCC could help fill this gap. The objective of this study was to characterize the immune landscape of canine OSCC to advance understanding of how dogs could serve as a surrogate for human OSCC. Canine OSCC contains a heterogenous tumor immune microenvironment. CD3+ T cells were the predominant tumor infiltrating immune cell population; however, there was a wide range CD3+ T cell density across samples. The most common CD3+ T cell micro-anatomical distribution was defined as “pre-existing immunity”, but the remaining 20% of tumors were characterized as “immunologically ignorant” or “excluded infiltrates” patterns. When compared to normal oral mucosa, the tumor gene expression pattern suggests that canine OSCC microenvironment is highly inflamed and characterized by the presence of an anti-tumor immune response dominated by cytotoxic\effector T cells and NK cells (CD8a, GZMA, OX40, and HLA-A); however, overexpression of genes associated with effector T cell exhaustion and microenvironmental immunosuppression was also identified (PD-1, LAG3, CXCL2). Correlations between CD3+ T cell density and immune gene expression revealed key genes associated with cytotoxic anti-tumor T cell responses (GZMA, GZMB, PRF1), co-stimulation of T cells (CD27, CD28, ICOS), and other immune processes, including Type I IFN response (TNF, TNFSF10), and T cell exhaustion (CTLA4, PD-1). CD3+ T cell density in canine OSCC was significantly correlated with a cytolytic activity score (mean PRF1 and GZMA expression), suggestive of active effector CD8 T cell function. CD204+ macrophages were the second most abundant tumor infiltrating immune cell, and when comparing to normal oral mucosa, two differently expressed genes linked to tumor associated macrophages and myeloid derived suppressor cells (MDSC) were identified: CXCL2, CD70. Overexpression of CXCL2 was also identified in canine OSCC “T cell-high” tumors compared to “T cell-low” tumors. This study identified actionable immunotherapy targets which could inform future comparative oncology trials in canine OSCC: CTLA-4, PD-1, CXCL2. These data provide a good first step towards utilizing spontaneous canine OSCC as a comparative model for human OSCC radiation and immuno-oncology research.